1997
DOI: 10.1021/bi9714363
|View full text |Cite
|
Sign up to set email alerts
|

Four Distinct Cyclin-Dependent Kinases Phosphorylate Histone H1 at All of Its Growth-Related Phosphorylation Sites

Abstract: In mammalian cells, up to six serines and threonines in histone H1 are phosphorylated in vivo in a cell cycle dependent manner that has long been linked with chromatin condensation. Growth-associated H1 kinases, now known as cyclin-dependent kinases (CDKs), are thought to be the enzymes responsible for this process. This paper describes the phosphorylation of histone H1 by four different purified CDKs. The four CDKs phosphorylate only the cell cycle specific phosphorylation sites of H1, indicating that they be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…The phosphorylation activity for these phosphorylation sites appeared to be independent of variant and site identity. The kinase for these phosphorylation sites has not been identified in human cells, but the equivalent peptide (SETAPAAPAAAPPAEK) is phosphorylated at both phosphorylation sites in a cell-cycle-specific manner by p38cdc2 in Chinese hamster ovary cells (50).…”
Section: Figmentioning
confidence: 99%
“…The phosphorylation activity for these phosphorylation sites appeared to be independent of variant and site identity. The kinase for these phosphorylation sites has not been identified in human cells, but the equivalent peptide (SETAPAAPAAAPPAEK) is phosphorylated at both phosphorylation sites in a cell-cycle-specific manner by p38cdc2 in Chinese hamster ovary cells (50).…”
Section: Figmentioning
confidence: 99%
“…We therefore chose this kinase, as well as the closely related Aurora A, as candidates to test in the subsequent assays. Although CDK1 was not predicted to be a putative H1.4S27 kinases, we decided to include it in our analyses as it has been shown that CDKs can phosphorylate serine and threonine residues in non-CDK consensus sites (Swank et al, 1997). We found that both recombinant Aurora A and Aurora B could phosphorylate H1.4 at S27 in vitro, whereas a CDK1-cyclinB1 complex could not (Fig.…”
Section: Aurora B Is a Mitotic H14s27 Kinasementioning
confidence: 99%
“…Although they have diverged much more than the core histones during evolution, linker histones in a wide variety of species typically contain numerous (S/T)PXZ motifs (where X is any amino acid and Z is a basic amino acid), and accordingly cyclin-dependent kinases have been investigated for their roles in H1 phosphorylation. Toward this end, the addition of Cdc2 kinase has been shown to cause premature chromatin condensation in some cell types, and decreased H1 phosphorylation following inhibition of cyclin-dependent kinases is associated with chromosome decondensation (22,23). However, because H1 phosphorylation and mitosis do not always occur simultaneously in certain organisms such as in Tetrahymena thermophila, the function of H1 phosphorylation has remained elusive.…”
Section: Molecular and Cellular Proteomics 5: 1593-1609 2006mentioning
confidence: 99%